Manajemen Risiko Pembiayaan Ijarah Pada Koperasi Syariah Pilar Mandiri Surabaya - Ahmad Asy’fin Basthomi; Achsania Hendratmi (Universitas Airlangga, 2017)
Sharia Financial Institution especially Sharia Cooperative needs a series of procedure and methodology which can be used to identify, measure, mitigate and supervise the risk that will be appear from business activity as well as in Ijara financing channeled. A series of procedures are known as risk management. The purpose of this study is to know and analyze how management process does on Sharia Cooperative of Pilar Mandiri Surabaya. This study uses qualitative approach with case study method. Data collection techniques uses direct interview technique to the related objects. The result of this study shows that Sharia Cooperative of Pilar Mandiri performed risk management process on the identification, mitigation, assessment or measurement and risk controlling stage. The major risk focus is financing risk that members or prospective members have congestion or failure about meet the financing payment obligation.